Treatment of MOG-IgG-associated disorder with rituximab: An international study of 121 patients - Whittam, Daniel H; Cobo-Calvo, Alvaro; Lopez-Chiriboga, A Sebastian; Pardo, Santiago; Gornall, Matthew; Cicconi, Silvia; Brandt, Alexander; Berek, Klaus; Berger, Thomas; Jelcic, Ilijas; Gombolay, Grace; Oliveira, Luana Micheli; et al. (Multiple sclerosis and related disorders, 2020)
•Largest study of rituximab in MOG-IgG-associated disorder, includes both adults and children.•Rituximab reduced relapse rates in MOG-IgG-associated disorder by 37%.•Compared to similar studies in AQP4-IgG-associated NMOSD, the efficacy seems lower.•Some patients relapsed despite apparent circulating B-cell depletion. To assess the effect of anti-CD20 B-cell depletion with rituximab (RTX) on relapse rates in myelin oligodendrocyte glycoprotein antibody-associated disorder (MOGAD). Retrospective review of RTX-treated MOGAD patients from 29 centres in 13 countries. The primary outcome measure was change in relapse rate after starting rituximab (Poisson regression model). Data on 121 patients were analysed, including 30 (24.8%) children. Twenty/121 (16.5%) were treated after one attack, of whom 14/20 (70.0%) remained relapse-free after median (IQR) 11.2 (6.3–14.1) months. The remainder (101/121, 83.5%) were treated after two or more attacks, of whom 53/101 (52.5%) remained relapse-free after median 12.1 (6.3–24.9) months. In this ‘relapsing group’, relapse rate declined by 37% (95%CI=19–52%, p<0.001) overall, 63% (95%CI=35–79%, p = 0.001) when RTX was used first line (n = 47), and 26% (95%CI=2–44%, p = 0.038) when used after other steroid-sparing immunotherapies (n = 54). Predicted 1-year and 2-year relapse-free survival was 79% and 55% for first-line RTX therapy, and 38% and 18% for second-/third-line therapy. Circulating CD19+B-cells were suppressed to <1% of total circulating lymphocyte population at the time of 45/57 (78.9%) relapses. RTX reduced relapse rates in MOGAD. However, many patients continued to relapse despite apparent B-cell depletion. Prospective controlled studies are needed to validate these results.